Addressing Military Sexual Violence by Proposing a Social Media Influencer Model - Cancio, Roberto (International journal of offender therapy and comparative criminology, 2021)
Military sexual violence (MSV) is a prevalent issue that uniquely affects mission readiness. Although research on MSV and social media is growing, examinations of possible interventions like those employing social media in this population are scant. Given the growing interest in targeting MSV, the present systematic review was conducted. The PRISMA framework was used to conduct a systematic review of MSV and social media (N = 71). Queries were limited to articles published between 2010 and 2020. SAGE Journals, PubMed, and JSTOR were utilized. Terms and potential combinations were entered into the databases in varying Boolean combinations. Additional recorders were identified for inclusion via the reference sections of relevant records. After removing duplicates from the query results, we selected records of suspected relevance by title and screened abstracts. Finally, articles with relevant abstracts were reviewed thoroughly to determine whether they met inclusion criteria for the review. The employments of military leaders in a social media intervention puts into practice the military’s central values and development of its leadership core. This intervention promotes group solidarity while maximizing conversations around meaningful messages. Findings in this review suggest military leaders could feasibly employ a cost-effective global intervention using social media, as a tool to help actively address MSV.